Developing Civil Society: Can we Expect NGO ? - Towar Ikbal Tawakkal, George; Lukman Hakim, M (International Journal of Engineering and Technology, 2018)
Democracies in some countries have stagnated because civil society failed to play their roles as controlling, watching, influencing policy, and so forth. The existence of civil society can not be separated from theÂ character of society. It means, developing civil society needs to consider the character of society.In Indonesia, some scholarsview one of civil societyâ€™s primary activity through observing NGO activities, demonstrations, and so forth. Institutionally, we can refer to them as civil society organizations. Socially, however, NGOs have trouble being part of society and society has no values to take people on demonstrations. In those situations, does it make sense to see the organizations and activities as civil society activities?. Based on evidencefrom some rural areas in Indonesia, this article will show that certain kinds of community leaders have major opportunities to lead civil society. They have strong social capital to play a major role in civil society, similar to Putnamâ€™s argument about social capital in civil society.Â While not perfect, these community leaders nonetheless complete some of the functions in civil society and, with their social capital, help develop civil society while NGOâ€™s have struggled to perform these same functions.Â Â